The Business Model Development of Qualbase (The Indonesian Journal of Business Administration, 2015)
Abstract.Qualbase is a start-up company providing information technology solution focused on small and medium enterprises (SMEs). As a start-up company, Qualbase did not understand how they should bring the company to grow and need guidance to reach their goals. Therefore, this final project aim to analyze Qualbase’s current business situation including company’s external and internal environment, develop appropriate business model as guideline for Qualbase including the implementation plan. In this final project, the author uses qualitative research method by interviewing Qualbase’s founder supported by additional secondary data from literatures, published journals, and other sources using internet media. The author uses several methods in analyzing Qualbase’s business condition. For company’s external environment analysis, the author use PEST, Porter’s five forces and competitor analysis. For company’s internal analysis, the author use VRIO framework and value chain analysis. The author then analyze and formulate business strategy using SWOT analysis, TOWS matrix, Porter’s generic business and business diamond strategy. Furthermore, the author formulate the appropriate business model for Qualbase using business model canvas and formulate the implementation plan based on business model development. As a result, the growth of industry where Qualbase operates is relatively good for company and has a growing market. Qualbase should focus on providing the best quality of products with excellence customer service. Additionally, Qualbase need to take appropriate action such as enhancing the quality of company’s resource and capability, develop standard operating procedures, create marketing strategies, improve online and social media campaigns and build relationship with clients.Keywords: Business Strategy, Business Model, Information Technology, SMEs